Gold-Catalyzed Intermolecular Oxidation of Terminal Alkynes: Simple and Efficient Synthesis of α-Mesyloxy Ketones - Xie, Longyong; Liang, Zhiwu; Yan, Dong; He, Weimin; Xiang, Jiannan (Synlett, 2013)
A variety of terminal alkynes were efficiently converted into the corresponding α-mesyloxy ketones through gold-catalyzed intermolecular oxidation in the presence of 3,5-dichloropyridine N-oxide as the oxidant. The reaction is proposed to proceed via α-oxo gold carbene intermolecular O–H insertion.
Keywords: alkynes; homogenous catalysis; gold; α-oxo gold carbine; α-mesyloxy ketones